0635 Vigilance Observations - Learning from Nighttime Driving Behaviours. (27th April 2018) - Tse, E; Bao, S; Campbell, M; Carson, N; Hussaina, H; Maher, K S; Beyzaei, N; Kemethofer, M; Seidenberger, M; Spruyt, K; Lewis, S; Ipsiroglu, O; et al.
Abstract: Introduction: Changes in vigilance are characteristic features of sleepless or sleep-deprived individuals. To standardize vigilance assessments, we reviewed videos of nighttime drivers with a structured rating system and investigated ratings of student observers. Methods: Nighttime driving videos of 60 adult volunteers recorded between 2 and 4 AM were provided by the Institute for Sleep-Wake-Research (ISWF, Vienna) and the Austrian Automobile Club (OEAMTC). Two 4.5-minute video recordings of 14 participants, after 30 and 90 minutes of driving, were analyzed. (A) Six observers rated participants using the Karolinska Sleepiness Scale (KSS); ratings were compared with drivers' self-ratings. (B) Open-ended and pictogram-based behaviours were annotated (O-a; P-a) and separated into (i) task-oriented (i.e. driving); (ii) non-task oriented (i.e. non-driving); and (iii) posture-oriented (e.g. stretching) behaviours. (C) Timing of (earlier versus later) videos were predicted. (D) Four videos were reviewed with a Delphi consensus process, determining to what extent pictograms could support analyses. Results: (A) KSS participant and observer ratings for the earlier (means, 3.0 vs. 4.25) and later recordings (mean, 6.5 vs. 6.1) were comparable, but not significant. (B) O-a and P-a revealed changes between the three behaviour categories as night progressed: task-oriented behaviours decreased; non-task oriented behaviours increased; and posture-oriented behaviours did not change. (C) However, observers failed to predict the timing of the two videos. (D) Discussions identified missing characteristic pictograms (e.g. self-stimulation) to inform future design. Conclusion: Although the KSS ratings corresponded and a change in task versus non-task oriented behaviours was detected, observers failed to correctly predict the timing of the videos. Causes of this discrepancy were explored and now self-stimulating behaviours and fluency of movements are being investigated. Support (If Any): BC Children's Hospital Research Institute and Foundation.